Performance Evaluation of a Semi-automated Method for [F-18]FDG Uptake in Abdominal Visceral Adipose Tissue - Stefanie A. de Boer; Daan S. Spoor; Riemer H. J. A. Slart; Douwe J. Mulder; Melanie Reijrink; Ronald J. H. Borra; Gerbrand M. Kramer; Otto S. Hoekstra; Ronald Boellaard; Marcel J. Greuter (SPRINGER, 2022)
Purpose
Severity of abdominal obesity and possibly levels of metabolic activity of abdominal visceral adipose tissue (VAT) are associated with an increased risk for cardiovascular disease (CVD). In this context, the purpose of the current study was to evaluate the reproducibility and repeatability of a semi-automated method for assessment of the metabolic activity of VAT using 2-deoxy-2-[F-18]fluoro-D-glucose ([F-18]FDG) positron emission tomography (PET)/x-ray computed tomography (CT).
Procedures
Ten patients with lung cancer who underwent two baseline whole-body [F-18]FDG PET/low-dose (LD) CT scans within 1week were included. Abdominal VAT was automatically segmented using CT between levels L1-L5. The initial CT-based segmentation was further optimized using PET data with a standardized uptake value (SUV) threshold approach (range 1.0-2.5) and morphological erosion (range 0-5 pixels). The [F-18]FDG uptake in SUV that was measured by the automated method was compared with manual analysis. The reproducibility and repeatability were quantified using intraclass correlation coefficients (ICCs).
Results
The metabolic assessment of VAT on [F-18]FDG PET/LDCT scans expressed as SUVmean, using an automated method showed high inter and intra observer (all ICCs >0.99) and overall repeatability (ICC=0.98). The manual method showed reproducible inter observer (all ICCs >0.92), but less intra observer (ICC=0.57) and less overall repeatability (ICC=0.78) compared with the automated method.
Conclusions
Our proposed semi-automated method provided reproducible and repeatable quantitative analysis of [F-18]FDG uptake in VAT. We expect this method to aid future research regarding the role of VAT in development of CVD.